Identifying factors influencing Iranian innovation ecosystem and determining their links - Shiva Javanmardi (Sustainable Futures, 2022)
BACKGROUNG AND OBJECTIVE: Economically and technologically powerful countries in today's world are those that progressed significantly in terms of scientific and technological developments. With technology and innovation come power and influence. To this end, Iran too must follow the same path towards innovation in producing science and technology. Therefore, a systemic view is required to align every component of the innovation ecosystem towards innovation based on a dynamic macro-, meso-, and micro-level strategic approach. The present study aims to identify and determine the links between components and subcomponents of innovation ecosystem. METHODOLOGY: A researcher-made questionnaire was used to survey a statistical population consisting of all department chairpersons and faculty members at four Iranian universities, namely University of Tehran and Shahid Beheshti University (as comprehensive universities) and Allameh Tabatabaei University and Amir Kabir University (as technical-professional universities) where a sample was selected through stratified random sampling. Quantitative analysis was conducted using descriptive and inferential statistics; the inferential part consisted of confirmatory factor analysis (CFA), structural equation modeling (SEM), and other techniques needed. The findings were analyzing in PLS using SEM combined at lower levels with first and second order CFA. Finally, components and subcomponents of innovation ecosystem were identified. FINDINGS: CFA results indicated that support and service, business, science and technology, finance and economy, sociocultural, policymaking and planning, innovative university, government, industry, and statutory-legal components were the most effective ones influencing innovation ecosystem where “support-service” (factor loading=0.92) was the most influencing while “statutory-legal (factor loading=0.52) was the least influencing factor when it comes to innovation ecosystem. DISCUSSION AND CONCLUSION: Therefore, an innovative ecosystem consists of a set of various components and factors interacting dynamically and continuously with one another and with the environment towards development of science, technology, and innovation, leading to overall growth of the ecosystem.